2018
DOI: 10.1007/978-3-319-94256-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Quantum Chaos Inside Black Holes

Abstract: We will argument how infalling information can be chaotized inside realistic quantum black holes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In the semiclassical regime, the partition function of a black hole can be related to an infinite sum of partition functions of conical singularities. Another side of this conjecture has been then proved in this paper, since we suggested that the presence of conical singularities can be related to the chaotization of infalling information [35,36,37,38]. This proposal then finds within this context a paradigmatic example.…”
Section: Conclusion and Remarksmentioning
confidence: 64%
See 3 more Smart Citations
“…In the semiclassical regime, the partition function of a black hole can be related to an infinite sum of partition functions of conical singularities. Another side of this conjecture has been then proved in this paper, since we suggested that the presence of conical singularities can be related to the chaotization of infalling information [35,36,37,38]. This proposal then finds within this context a paradigmatic example.…”
Section: Conclusion and Remarksmentioning
confidence: 64%
“…It is also worth to note that in Refs. [35,36,37,38] a relation between conical singularities and chaotization of infalling information was pointed out. Indeed, the chaotization phenomenon can be recast from the prospective of the eikonal scattering, confirming the conjecture of Refs.…”
Section: )mentioning
confidence: 99%
See 2 more Smart Citations
“…Of course CP 2 , K 3 can be inversely oriented, two possible antibubbles CP 2 , K3. S 2 × S 2 has (χ, τ ) = (4, 0), CP 2 has (3, 1), CP 2 has (3, −1) K3 has (24,16) and K3 has (24, −16). In space-time with a spin structure, CP 2 , CP 2 are not possible.…”
mentioning
confidence: 99%